2011
DOI: 10.2134/jeq2010.0141
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Herbicides and Veterinary Antibiotics Losses from Agroecosystems Using Vegetative Buffers

Abstract: Multiple species vegetative buffer strips (VBSs) have been recommended as a cost-effective approach to mitigate agrochemical transport in surface runoff derived from agronomic operations, while at the same time offering a broader range of long-term ecological and environmental benefits. However, the effect of VBS designs and species composition on reducing herbicide and veterinary antibiotic transport has not been well documented. An experiment consisting of three VBS designs and one continuous cultivated fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 35 publications
2
79
2
Order By: Relevance
“…It suggested that the concentrations of ofloxacin and enrofloxacin were less than other antibiotics currently, but they increased quickly. Recently, ofloxacin and enrofloxacin were frequently detected in sediments or soil [34,35], which supported the accumulation growth factor in this work. In contrast, the accumulation growth factors of oxytetracycline, ciprofloxacin and gentamicin were less than one suggesting their contamination decreased.…”
Section: Screening-out Of Priority Antibioticssupporting
confidence: 88%
“…It suggested that the concentrations of ofloxacin and enrofloxacin were less than other antibiotics currently, but they increased quickly. Recently, ofloxacin and enrofloxacin were frequently detected in sediments or soil [34,35], which supported the accumulation growth factor in this work. In contrast, the accumulation growth factors of oxytetracycline, ciprofloxacin and gentamicin were less than one suggesting their contamination decreased.…”
Section: Screening-out Of Priority Antibioticssupporting
confidence: 88%
“…In this context, implantation of man-made riparian buffer strips (RBS) at the boundary of the agricultural lands may limit runoff and decrease water contamination. The ability of these plants to perform efficient root uptake of these agricultural wastes plays an important role in RBS efficacy (Krutz et al, 2005;Lin et al, 2011). It was advance that glyphosate may compete with PO 4 3− for membrane carriers (Denis and Delrot, 1993;Morin et al, 1997), as it occurs with soil absorption sites.…”
Section: Mainmentioning
confidence: 99%
“…Because these factors vary considerably between studies, a wide range of mitigation efficiencies have been reported in the literature for herbicides. For example, reductions in ATR transport by VBS varied from 11 to 100% of the applied mass (USDA‐NRCS, ; Popov et al ., ; Zhang et al ., ; Lin et al ., 2011a). Of the various factors involved, those that can be managed include vegetation type, buffer width, and buffer placement.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of VBS to reduce surface transport of organic contaminants is affected by numerous factors, including soil properties, buffer width, source to buffer area ratio (SBAR), buffer placement, runoff regime ( i.e ., sheet vs . concentrated flow), slope, rainfall intensity, antecedent soil water content, buffer vegetation, and the chemical properties of the contaminant (Reichenberger et al ., ; Lin et al ., , 2011a; Zhang et al ., ). Because these factors vary considerably between studies, a wide range of mitigation efficiencies have been reported in the literature for herbicides.…”
Section: Introductionmentioning
confidence: 99%